2017
DOI: 10.2174/1389450117666160112115641
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Pathway as Drug Targets in Cancer Therapy and Regenerative Medicine

Abstract: Yes-associated protein 1 (YAP1) and transcriptional co-activator with PDZ-binding motif (TAZ) co-operate with numerous transcription factors to regulate gene transcriptions. YAP1 and TAZ are negatively regulated by the tumor suppressive Hippo pathway. In human cancers, the Hippo pathway is frequently deregulated and YAP1 and TAZ escape the inhibition by the Hippo pathway. The upregulation of YAP1 and TAZ induces epithelial-mesenchymal transition and increases drug resistance in cancer cells. TAZ is implicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…Our previous studies confirmed that TAZ and its activator promoted muscle differentiation and resisted muscular atrophy, based on in vivo animal models of muscular atrophy induced by toxins, glucocorticoids[10], traumatic brain injury[16], disuse, starvation, and cancer-related cachexia[30]. These results suggest the potential of TAZ activators for treatment of muscle atrophy.…”
Section: Discussionsupporting
confidence: 78%
“…Our previous studies confirmed that TAZ and its activator promoted muscle differentiation and resisted muscular atrophy, based on in vivo animal models of muscular atrophy induced by toxins, glucocorticoids[10], traumatic brain injury[16], disuse, starvation, and cancer-related cachexia[30]. These results suggest the potential of TAZ activators for treatment of muscle atrophy.…”
Section: Discussionsupporting
confidence: 78%
“…This protein, along with its partner PDZ-binding domain taffazin, orchestrate the Hippo pathway[ 147 ]. In principle, hippo signalling plays an important role in the regulation of tissue homeostasis, development, regeneration, and cancer[ 148 ]. Three protein components in mammals are depicted: Mammalian Ste 2 like kinase 1 and 2, and large tumor suppressor kinase 1 and 2.…”
Section: Notch Signalling In Colorectal Cancermentioning
confidence: 99%
“…If yes, it would be important to check if other components of the Hippo signaling pathway are also involved in the formation of invadopodia. This could constitute another mechanism through which the Hippo signaling pathway impinges on cancer cell organization and metastasis [8] [9].…”
Section: Resultsmentioning
confidence: 99%